Some interesting observations regarding TB patient management from a rural area of Madhya Pradesh: TB case series - Akash Ranjan Singh; Abhijit Pakhare; Ashish Chauhan; Abhishek Singh (Journal of Family Medicine and Primary Care, 2015)
Despite many serious efforts, tuberculosis (TB) is still a recognized public health problem. The Government of India has adopted the Directly Observed Treatment, Short-Course (DOTS) strategy for the entire country through the Revised National Tuberculosis Control Programme (RNTCP) for the treatment of TB. In this report, we have presented the trajectories for care seeking of two TB cases who suffered from either "patient level delays" or "health system-related delays" in seeking DOTS for the treatment of TB.